THE INFLUENCE OF ISLAMIC PHILOSOPHY ON WESTERN INTELLECTUAL TRADITION: A HISTORICAL PERSPECTIVE - Sahjad M. Aksan; Samantha Gonzales; Josefa Flores (Yayasan Adra Karima Hubbi, 2026)
The historical narrative of Western intellectual development often obscures the profound contributions of Islamic philosophy, frequently reducing the Islamic Golden Age to a mere preservation period for Hellenistic thought. This research aims to re-evaluate the specific mechanisms and depth of Islamic influence on the Western intellectual tradition, specifically during the Scholastic revolution. A qualitative historical-philosophical design was employed, utilizing hermeneutic analysis and diachronic mapping of primary Arabic texts and their subsequent Latin translations. Findings reveal that Muslim polymaths like Ibn Sina and Ibn Rushd were not passive conduits but original innovators who provided the metaphysical and logical scaffolding for Western Scholasticism. The study identifies a systematic “transcultural synthesis” where Islamic rationalism fundamentally restructured European epistemology, particularly regarding the distinction between essence and existence and the development of empirical methodologies. This research concludes that the Western philosophical canon is a hybrid construct deeply rooted in Islamic intellectual labor, necessitating a decolonized approach to the history of ideas. Recognizing this shared heritage challenges Eurocentric biases and promotes a more inclusive understanding of global human progress.